(untitled) (Scientific journal of the Fergana State University, 2023)
It is known that in the methodology of the Enlightenment of the Soviet period, one of the important tasks was the training of teaching staff on the basis of the idea of communism, the dissemination of the ideas of the Communist Party and the upbringing of the future generation. therefore, the activities of secondary schools consisted mainly in the integration of the idea of "developed socialism" into students, educating them in the "Communist spirit". The information on the specific methods of the Soviet period education system in this article, the decisions taken to improve the level of material availability of school teachers, the appearance and general activities of teachers were covered on the basis of davriy publications, archival materials.